Description of Malnutrition and Stunting in Pediatric Patient in Sakura Ward - Subardi, Arda Yunita; Yunilasari, Yunilasari; Nitroh, Nur Nida; Komarudin, Heru; Rahmanida, Nindya; Rahmadani, Putri (Jurnal Penelitian Perawat Profesional, 2025)
Malnutrition and stunting conditions in pediatric patients undergoing hospitalization also contribute to the increase in morbidity, mortality, length of treatment, and health costs. This Study aims to identify the characteristics of children with severe malnutrition and stunting in the inpatient ward of RSUD Bekasi in 2023. A descriptive cross-sectional study conducted from January to December 2023 in the Sakura inpatient ward of RSUD Bekasi. Data were collected from a total sample 343 patients based on nutrition records and reports, including patients aged 0-18 years who were hospitalized during the period in 2023. The data were then analysed to determine the proportion of malnutrition and stunting based on age, length of stay, and medical diagnosis. The result show proportion of malnutrition and stunting is highest among patients aged 0-3 years (64.8%), a length of stay ≤7 days (64.8%) being far more common than those with a length of stay >7 days (35.2%). Pediatric patients with malnutrition and stunting are in the medical diagnosis group of gastrointestinal disorders (28.6%), and respiratory disorders (20.9%). This indicates that patients with malnutrition and stunting require more attention improve their nutritional status and address complication to order to reduce the length of hospital stay.